Analysis of real-time PCR cycle threshold of α-thalassemia-1 southeast asian type deletion using fetal cell-free DNA in maternal plasma for noninvasive prenatal diagnosis of bart's hydrops fetalis - Sakorn Pornprasert (2018)
Background: Noninvasive prenatal diagnosis based on detection of fetal cell-free DNA is hampered when mother and father are both carriers for the same autosomal recessive mutation. Objective: To compare the diagnosis of Bart's hydrops fetalis using conventional Gap-PCR analysis of fetal cells/tissues with the measurement of quantitative difference (ΔCT) between α-thalassemia-1 SEA type deletion gene (CT-mutant) and wild type α-globin gene (CT-wild type) in plasma of pregnancies by using the Taqman real-time quantitative PCR. Material and Method: Plasma DNA samples were collected from three groups of pregnancies whose fetuses have known thalasemia status (7 normal, 11 heterozygote α-thalassemia-1 SEA type deletion, and 7 Bart's hydrops fetalis). The α-thalassemia-1 SEA type deletion gene and wild type α-globin gene were quantified by using Taqman real-time quantitative PCR and then the ΔCT was analyzed by subtracting the CT-mutant from CT-wild type. Results: Mean ΔCT values were not significantly different among the three groups. However, women whose fetuses were diagnosed as Bart's hydrops fetalis had a higher proportion (43%) of plasma DNA samples that had negative ΔCT value than women whose fetuses were diagnosed as normal or heterozygote α-thalassemia-1 SEA type deletion (0 and 27%, respectively). Conclusion: Further investigations are needed to improve the diagnosis of Bart's hydrops fetalis using fetal cell-free DNA.